HUBUNGAN MANAJEMEN STRES DENGAN BURNOUT SYNDROM DAN MOTIVASI KERJA PERAWAT DI RUANG ICU - Tri Lestari Handayani; Dessi Natallina; Jamaludin (Optimal Nursing Journal, 2026)
Introduction: Intensive Care Unit (ICU) nurses are highly vulnerable to occupational stress due to the complexity and urgency of patient care, which may lead to burnout syndrome and decreased work motivation. Effective stress management is essential to maintain nurses’ psychological well-being and performance. However, evidence examining the interplay between stress management, burnout, and work motivation among ICU nurses remains limited. Methods: This study employed a quantitative correlational design with a cross-sectional approach. A total of 50 ICU nurses aged 25–40 years, with 1–10 years of work experience, were recruited. Data were collected using a stress management questionnaire, the Maslach Burnout Inventory (MBI), and a work motivation questionnaire. Statistical analysis was conducted using Chi-square and Fisher’s Exact Test to determine the relationships between variables. Results: The findings revealed a significant relationship between stress management and burnout syndrome (p = 0.012; OR = 0.9), indicating that nurses with good stress management had lower odds of experiencing burnout. Additionally, a significant relationship was found between stress management and work motivation (p = 0.049; OR = 2.9), suggesting that nurses with good stress management were more likely to have higher work motivation.Discussion/Suggestion: Effective stress management plays a critical role in reducing burnout and enhancing work motivation among ICU nurses. Healthcare institutions should implement structured stress management training programs to support nurses’ mental well-being and optimize their professional performance